Ternary coordination and spatial convergence of digital economy, green finance, and green urbanization in the Yellow river basin of China - Ma, Rong; Xi, Cunhu; Li, Yajing (Frontiers in Environmental Science, 2025)
This study examines the interplay and spatial convergence of the digital economy, green finance, and green urbanization in the Yellow River Basin from 2001 to 2022, with a focus on their roles in promoting sustainable development. Utilizing a “pattern-process-mechanism” framework, the study employs the Global Moran Index, the Dagum Gini Coefficient, and the β-convergence model to analyze spatiotemporal dynamics and the coupling coordination across 77 cities in the region. The findings reveal a steady improvement in coordination, primarily driven by advancements in the digital economy, although regional disparities remain. Downstream cities benefit from industrial and resource advantages, while upstream areas continue to face significant challenges. The β-convergence analysis further suggests a narrowing of the regional gap, with spatial factors playing a key role in enhancing coordination. Based on these results, policy recommendations include strengthening regional cooperation, optimizing industrial structures, and increasing government support to foster balanced green development. These insights provide both theoretical and practical guidance for the formulation of sustainable economic strategies in ecologically sensitive regions.